Reflective structured dialogue as a tool for addressing wicked public health problems - Cassidy Weaver; Janaya Brown; Lexi Brady; Parker Carlquist; Seth Dotson; M. Dru Faldmo; P. Cougar Hall; Jeffrey Glenn (Frontiers Media S.A., 2023)
IntroductionAttempts to address wicked public health problems can benefit from collaborative approaches to problem-solving, such as dialogue through structured conversations, that engage a wide range of stakeholders in deliberate inquiry to build trust and mutual understanding. This study seeks to assess the effects of participation in Reflective Structured Dialogue (RSD) on university students' polarization-related attitudes.MethodsThe BYU Campus Conversations project held 27 structured conversations with 139 participants on three divisive public health topics: COVID-19, mental health, and racism. The conversation structure encouraged students to share their personal experiences and learn from others in an environment that promoted vulnerability and confidentiality.ResultsPre- and post-conversation surveys measured participant outcomes and found that participation in conversations was strongly associated with improved attitudes related to openness, tribal identity, and moral disdain. Over 95% of participants reported that they enjoyed taking part in the conversations and that it helped them better understand the experiences of others.DiscussionThe results of this project indicate similar conversations could be an effective tool in helping build understanding around divisive public health issues in university and community settings.